Potential Antibacterial Agents: 4-Thiazolidinone Derivatives - Solankee, Anjani; Kapadia, Kishor; Mistry, Pankaj; Patel, Jayesh (Asian Journal of Chemistry, 2010)
The cycloaddition reaction of thioglycolic acid with Schiff basesgives the corresponding 4-thiazolidinones. 4-Thiazolidinone derivativeson condensation with 3,4,5-trimethoxy benzaldehyde resultedin benzylidene derivatives of 4-thiazolidinones. The synthesisedcompounds were characterised on the basis of elemental analysisand spectral studies and tested in vitro against E. coli, S. aureus,S. thyphi and E. aerugenes for their antibacterial activity.